Teaching in tandem : effective co-teaching in the inclusive classroom - Wilson, Gloria Lodato (ASCD, 2011)
This book focuses on creating a successful partnership while co-teaching within a classroom, and examines topics such as organization, engaging students with multiple perspectives, and responding to parental concerns. Provides guidance based on answering questions posed by real co-teachers, and is suitable for principles, teachers, paraprofessionals, and administrators.